STRATEGIC CHALLENGES AND EMERGING PERSPECTIVES IN SUPPLY CHAIN MANAGEMENT - Sivakumar G; Premrajkumar E (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The field of supply chain management (SCM) has experienced significant evolution; however, it continues to face a multitude of challenges and perspectives that impact its overall effectiveness. Traditional approaches have predominantly concentrated on minimizing expenses and improving operational efficiency, often resulting in linear and compartmentalized processes that exhibit limited flexibility and responsiveness. Among the primary challenges are disruptions instigated by global occurrences, escalating consumer expectations for rapidity and customization, and the complexities associated with managing a diverse array of suppliers. Additionally, reliance on historical data for forecasting purposes may yield inaccurate predictions, exacerbating issues related to inventory management. Contemporary perspectives advocate for the adoption of integrated and agile systems that employ technological advancements, including sophisticated analytics and real-time data, to enhance decision-making and foster collaboration. By emphasizing sustainability and risk management, modern SCM frameworks aim to cultivate resilient supply chains capable of swiftly adapting to fluctuating market conditions. Addressing these challenges requires a transition from conventional methodologies to more innovative and holistic strategies that prioritize collaboration, transparency, and adaptability within supply chain operations.